(untitled) (Faridpur Medical College Journal, 2017)
Melasma is characterized by melanosis with sharply demarcated blotchy, brown macules usually in a symmetric distribution over the cheeks and forehead and sometimes on the upper lip and neck. It is most often seen in women during pregnancy, at menopause and while taking oral contraceptives; it occasionally occurs in women who are not pregnant or taking oral contraceptives, as well as men. So it is a great problem in our country. A clinical trial was conducted to find out the effect of the combination of 20% azelaic acid with 0.05% tretinoin cream in the treatment of melasma. Twenty clinically diagnosed cases of melasma attending the outpatient department of Dermatology and Venereology, Faridpur Medical College Hospital, Faridpur were enrolled. Majority of the study subjects (40%) were between 26 to 30 years of age and most of them (60%) were females. Regarding occupation, 60% were housewife. Out of the study subjects 75% were married and 60% were middle class. Around 60% cases had positive family history of melasma and maximum (90%) patient had no history of systemic drug and the maximum (80%) patients had no history of use of cosmetics. It was observed that highest (90%) number of patients had malar area involvement and 10% had centro-facial area involvement. The study showed moderate reduction of the severity of melasma after the treatment. Out of the study subjects, 40% and 20% developed burning sensation and erythema respectively. It could be concluded that combination of 20% azelaic acid and 0.05% tretinoin cream, has a moderate lightening effect in the treatment of melasma. Faridpur Med. Coll. J. Jul 2016;11(2): 50-53